Teachers’ Strategies in Managing the Use of Mobile Phone in the Classroom - Riza, Armilia; Afriyanti, Rika; Sevrika, Hevriani (JUPE : Jurnal Pendidikan Mandala, 2025)
This research describes how teachers manage students' use of mobile phones in the classroom. They need a planned and structured strategies to minimise disruption and improve student learning outcomes. Teachers at SMA N 1 Kinali implemented various strategies, such as scheduled mobile phone use, involving parents or guardians, making clear rules, giving rewards, monitoring using monitoring apps, and confiscating mobile phones. The researcher found that involving parents and/or guardians, clear rules, providing rewards, monitoring using monitoring applications are important strategies in managing students' mobile phone use to maintain focus and learning effectiveness. It can be concluded that the implementation of effective management strategies not only reduces distractions, but also ensures technology is used optimally to support the learning process.